Color semantics in traditional japanese culture (Journal of Oriental Studies, 2018)
In different cultures color has several symbolic meanings and is interpretedbased on customs and traditions and behavioral norms of the people.Semiotics of color contributes to the opening of the traditional culturefundamentals. The article analyzes conception of color which dominates inJapanese language and culture, and also emphasizes color which is on thepole position. Historic and sociocultural examples mentioned in the articleopen the idea of color hierarchy in Japanese culture.